Bibliometric analysis of research on digestive system tumors and depression - Ying Qu; Duorui Nie; Yuwei Song; Xiaojun Cai; Yilin Gong; Sheng Chen; Jia Ye; Jing Li (Frontiers in Psychology)
BackgroundMalignant tumors of the digestive system pose a serious threat to human health due to their highly malignant nature. Depression, as the most common psychiatric symptom of digestive system tumors, has attracted much attention regarding its potential relationship with these tumors. A thorough investigation into the connection between digestive system tumors and depression is extremely important for strengthening patients’ quality of life and treatment outcomes.MethodsFrom 2014 to 2023, we conducted a literature search using specific keywords in the Web of Science Core Collection (WoSCC) and performed visual analysis of the selected literature using Microsoft Excel, CiteSpace, and VOSviewer software. In this study, we analyzed countries, institutions, authors, journals, and keywords.ResultsA total of 384 research articles on the relationship between digestive system tumors and depression were identified. The number of publications showed a gradual increase over time. In terms of disciplinary distribution, Oncology, Health Care Sciences Services, and Medicine General Internal ranked top in terms of publication volume. In terms of geographical distribution, China and the United States were the countries contributing the most publications. Additionally, Maastricht University contributed the most publications. Regarding authors, Beekman, Aartjan T.F. and Dekker, Joost had the highest number of publications, while Zigmond, A.S. had the most citations. It is worth mentioning that Supportive Care in Cancer was the journal with the most publications in this field. In terms of keyword analysis, research mainly focused on mechanisms and treatment strategies related to the relationship between digestive system tumors and depression.ConclusionThe relationship between digestive system tumors and depression has become a new research hotspot in recent years, offering new directions for future research. This research reveals novel perspectives on comprehending the connection between the two, which can guide future research and practice.